Suitability analysis of assembled solar greenhouses in northwest China based on CFD - Wu, Xiao; Jia, Kai; Xu, Hongjun; Li, Hong; Zhang, Weihua (International Journal of Agricultural and Biological Engineering, 2025)
Solar greenhouses in China have various structural forms. Compared with traditional solar greenhouses, the assembled solar greenhouse is not only simple in construction, convenient and fast in installation, but also improves the utilization efficiency of land and reduces the damage to the soil layer, cleverly achieving the transformation between plastic greenhouses and solar greenhouses. To determine the regions suitable for promoting modular solar greenhouses, this study adopts a combination of actual measurement and simulation methods. Based on Autodesk CFD software, a dynamic thermal model of modular solar greenhouse is established. Predictions and adaptive analysis of indoor temperature field changes at different regions are conducted in the consideration of boundary conditions such as outdoor air temperature, solar radiation on walls, and ground in various regions. The experimental results show that the change trends of measured and simulated values are basically consistent, indicating a high degree of model agreement. The maximum average deviation between the predicted and measured values of indoor air temperature is 1.53°C, the maximum average absolute deviation is 2.52°C, and the maximum root mean square is 3.74°C. The absolute coefficient ranges from 0.84 to 0.92, which indicates that the model can accurately reflect the temperature field distribution and heat exchange situation of the modular solar greenhouse at different times. This study provides a theoretical basis for the application and promotion of modular solar greenhouses and also offers a new research method for suitability simulation analysis of other types of solar greenhouses. Keywords: assembled solar greenhouses, suitability analysis, northwest China, CFD DOI: 10.25165/j.ijabe.20251804.9289Citation: Wu X, Jia K, Xu H J, Li H, Zhang W H. Suitability analysis of assembled solar greenhouses in northwest China based on CFD. Int J Agric & Biol Eng, 2025; 18(4): 78–88.